2001
DOI: 10.1007/pl00002938
|View full text |Cite
|
Sign up to set email alerts
|

Increased urinary albumin excretion and its associations in the WHO Multinational Study of Vascular Disease in Diabetes

Abstract: Centres varied widely in the prevalence of increased albumin excretion but associations with risk factors and vascular complications were generally similar in most centres and in both major types of diabetes with ethnic and genetic differences probably contributing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
26
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 14 publications
3
26
2
Order By: Relevance
“…The high renal failure rate in American Indians has been reported previously and is consistent with the higher incidence of renal failure in this group [4]. Our analysis shows that plasma glucose appears to be the most important determinant of this increased risk and suggest that triglycerides could also be involved (Table 4).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The high renal failure rate in American Indians has been reported previously and is consistent with the higher incidence of renal failure in this group [4]. Our analysis shows that plasma glucose appears to be the most important determinant of this increased risk and suggest that triglycerides could also be involved (Table 4).…”
Section: Discussionsupporting
confidence: 91%
“…With over 43 670 person years of follow-up it is in a unique position to provide information on risk factors for renal failure. Another paper in this supplement focuses on risk factors for and prevalence of albuminuria, an early marker of renal failure, for which only prevalence data rather than incidence data were available [4].…”
mentioning
confidence: 99%
“…The reported prevalence of microalbuminuria in this group, 39.8%, is remarkably high; higher than the prevalence reported in other populations [2]. However, it should be noted that the method used to identify microalbuminuria in this study was a semi-quantitative test (Micral test; Roche Diagnostics, Mannheim, Germany), which is considered a screening, but not a diagnostic, test for microalbuminuria.…”
contrasting
confidence: 56%
“…revious studies have reported a marked variation in the prevalence of microalbuminuria in type 2 diabetic patients ranging from 7 to 47% (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). The variation could arise from ethnic/genetic differences in susceptibility (3)(4)(5)(6)(7)(8)(9)(10)(11) and from methodological issues for investigating the prevalence, such as small-sized populations (3,12,13); single clinic-based studies (8,12); use of the dipstick method instead of quantitative determinations (4,5); or only a single measurement of urinary albumin excretion (UAE) (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13), whereas multiple measurements have been recommended for years (14).…”
mentioning
confidence: 99%